A matheuristic approach for the family traveling salesman problem - Abtin Nourmohammadzadeh; Malek Sarhani; Stefan Voß (Journal of Heuristics, 2023)
In the family traveling salesman problem (FTSP), there is a set of cities which are divided into a number of clusters called families. The salesman has to find a shortest possible tour visiting a specific number of cities from each of the families without any restriction of visiting one family before starting the visit of another one. In this work, the general concept of the Partial OPtimization Metaheuristic Under Special Intensification Conditions is linked with the exact optimization by a classical solver using a mathematical programming formulation for the FTSP to develop a matheuristic. Moreover, a genetic and a simulated annealing algorithm are used as metaheuristics embedded in the approach. The method is examined on a set of benchmark instances and its performance is favorably compared with a state-of-the-art approach from literature. Moreover, a careful analysis of the specific components of the approach is undertaken to provide insights into the impact of their interplay.
Keywords: 510; Matheuristic; Partial optimization metaheuristic under special intensification conditions; Genetic algorithm; Family traveling salesman problem